PENGARUH LATIHAN DOUBLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI PADA EKSTRAKURIKULER LOMPAT JAUH PUTRA SMP SANTA THERESIA AIR MOLEK - Evy Yeti Nadia Galama Sihotang; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
The problem in this study is that there is still a lack of long jump ability, especially in leg muscle power, even though the techniques are already quite good, but when doing repulsion, it still needs to be improved. To fix this problem, the authors provide a form of exercise that increases power, especially in the leg muscles, namely the double leg speed hop exercise. The title raised in this study is "The Effect of Double Leg Speed Hop Exercise on Leg Muscle Power in Men's Long Jump Extracurricular at SMP SANTA THERESIA Air Molek" so that in the future these students can do long jumps well, and the most important thing after this research is to know Is there an increase in long jump ability especially in leg muscle power. The form of this research is (using a one group pretest-postest design approach) with a population of 10 male long jump extracurricular activities at SMP SANTA THERESIA Air Molek, totaling 10 people. The instrument used in this study was a standing board jump test which aims to determine the effect of double leg Speed Hop training on leg muscle power. After that, the data were processed statistically, to test for normality using the Lilliefors test at a significant level of 0.05α. The hypothesis proposed is that there is an effect of double leg speed hop training on leg muscle power in the male long jump extracurricular at SMP SANTA THERESIA Air Molek. Based on the data normality test analysis, the pre-test results resulted in a Lcount of 0.1156 and an Ltable of 0.258, which means that Lcount <Ltable. while the post-test data resulted in a Lhitung equal to 0.1056 and an L-table of 0.258 means that the Lcount <Ltable, then the data were normally distributed. Based on statistical data analysis, there is a pre-test average of 1,820 and a post-test average of 2,026. Then based on the t-test analysis, the t-test value is 4.2 and the t-table is 1.812, then tcount> ttable then Ho is rejected and Ha is accepted. Thus it can be concluded that there is an effect of double leg speed hop training on leg muscle power in the male long jump extracurricular at SMP SANTA THERESIA Air Molek.Key Words: Double Leg Speed Hop Exercise, Leg Muscle Power